Confinement and Electrocatalysis of Cerium Fluoride Nanocages to Boost the Lithium–Sulfur Batteries Performance. Issue 8 (8th June 2022) - Liu, Liwei; Guo, Yue; Qi, Zhihao; Zeng, Yu; Cheng, Xueyi; Yang, Lijun; Wu, Qiang; Wang, Xizhang; Hu, Zheng
Abstract : Lithium–sulfur batteries (LSBs) are beset by the polysulfides shuttling and the sluggish conversion kinetics, leading to fast capacity fading and inferior rate capability. A feasible solution is to confine the active species and/or electrocatalytically boost the polysulfides conversion by suitable host materials. Herein, hollow cerium fluoride nanocages (h‐CeF3 ) are employed as the host, which not only suppressed polysulfides shuttling via physical confinement and chemisorption, but also exhibited remarkable catalytic promotion to the polysulfide conversion, much superior to the counterparts of solid cerium fluoride nanodiscs (s‐CeF3 ) and hollow ceria nanospheres (h‐CeO2 ). Consequently, the sulfur‐filled h‐CeF3 cathode delivers an outstanding capacity of 544 mAh g −1 at 5 A g −1, demonstrating a high rate capability. With an areal sulfur loading of ≈3.5 mg cm −2, the LSB exhibits a reversible capacity of 429.5 mAh g −1 at 1 A g −1 after 200 cycles under a low electrolyte/sulfur (E/S) ratio of 10 μL mg −1 . This study demonstrates the promise of the h‐CeF3 host in Li–S batteries, shedding light in developing advanced sulfur hosts of metal fluorides. Abstract : Hollow CeF3 nanocages are employed as the sulfur host for the first for lithium–sulfur batteries (LSBs), which exhibits the synergism of the physical confinement and strong chemisorption for polysulfides, as well as the high electrocatalytic activity for polysulfide conversion, leading to the excellent rate and cycling performances.